Electrospun nanofiber nerve guidance conduits for peripheral nerve regeneration: A review. (5th December 2022) - Lee, Sangjoon; Patel, Madhumita; Patel, Rajkumar
Graphical abstract: Abstract: Peripheral nerve injuries (PNIs) often lead to permanent impairment of functional movement and sensory loss due to limited effective treatment options. Currently, autologous nerve grafting has been widely used in practice, however it remains challenging due to pre-and post-surgery issues such as limited availability of donor nerve tissue, size mismatch, and donor site morbidity. Moreover, these issues are further exacerbated in treating PNIs with larger nerve gaps. To overcome the challenges associated with autologous nerve grafting, a treatment method with artificial nerve guidance conduits (NGCs) has been developed as a promising alternative technique. Tubular in shape, an NGC bridges the two ends of damaged nerves and provides directional guidance and physical protection for axonal growth and nerve elongation. Nanofibrous NGCs resemble the structural environment of the endogenous extracellular matrix (ECM) with the use of electrospun nanofibrous scaffolds. With new advances in the electrospinning technique, novel NGCs designs are proposed for greater functional recovery. This review covers peripheral nerve regeneration efficacy of electrospun NGCs exhibited in vivo and in vitro studies. NGCs with varying polymer compositions, simulating agents, and electrical stimulation were compiled.